The Influence of Profitability And Insider Ownership On Firms Value With The Debt Policy As Intervening Variable (Empiric Study On Public Company In Indonesia Stock Exchange Period 2009-2012) - Risa Wulandari; Sutrisno T (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to determine the influence of profitability and insider ownership on firm value that mediated by debt policy (leverage). Data that used was secondary data of 82 public companies in Indonesia Stock Exchange (BEI) with 4 years period, since 2009 till 2012. Using mediated path model, this research tried to test the theory in line with research purpose. The instrument of the analysis used was Smart PLS programs. Result finding indicated profitability positively and significantly on firm value and debt policy. Insider ownership negative and not significantly to debt policy but positively and significantly to firm value, meanwhile debt policy has negative and significantly effect to firm value. Finally, simultaneously debt policy couldn’t successfully mediate profitability and insider ownership on firm value. This research finding also oppose against with static tradeoff theory. Static trade off theory focuses discussion at trade off between cost of debt and benefit of debt (Huang and Ritter, 2004). Static trade off assumed that capital structure of company is determined by considered tax-deductible benefit when increasing level of debt and increasing level of agency cost in other side. Keywords: profitability, insider ownerships, debt policy (leverage), firm value